Women in Construction Sector: An Integrative Literature Review and SWOT Analysis for Strategic Development - Irika Widiasanti; Iris Mahani; Yunita Afliana Messah; Selvia Agustina (International Journal of Engineering, Science and Information Technology, 2026)
Women's participation in the construction sector remains significantly low on a global scale. This persistent underrepresentation is primarily driven by multiple systemic barriers that severely limit career advancement, retention, and professional development for female practitioners. Consequently, there is a critical need for comprehensive systematic analysis and strategic solutions to address these challenges within the architecture, engineering, and construction (AEC) industries. This study aims to systematically analyze the multifaceted challenges, emerging opportunities, and practical strategic solutions for enhancing women's involvement in the construction industry through an integrative methodological approach. The research methodology encompasses a comprehensive integrative literature review combined with a robust SWOT analysis framework, involving extensive database searches across major academic repositories, strict quality assessments, and systematic data extraction. The findings identify critical internal barriers such as workplace discrimination, safety concerns, work-life balance challenges, and limited career progression pathways. However, favorable external opportunities such as technological advancements, evolving industry policy reforms, and severe labor shortages creating high demand provide viable avenues for long-term professional growth and integration. Furthermore, this research proposes structured strategic development pathways, including targeted training programs, flexible work arrangements, institutionalized mentoring, and the cultivation of an inclusive organizational culture. By bridging the gap between internal diagnostics and external environmental scanning, this paper contributes an evidence-based strategic framework and actionable recommendations for diverse industry stakeholders. Ultimately, it fosters a sustainable development pathway for gender equality, ensuring that women's participation is recognized not merely as a compliance measure, but as a strategic catalyst for long-term industry innovation, workforce resilience, and overall organizational efficiency in the built environment